2015
DOI: 10.1186/s13071-015-1253-z
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the artemisinin resistant marker (K13) in Plasmodium falciparum parasite populations of Grande Comore Island 10 years after artemisinin combination therapy

Abstract: BackgroundPlasmodium falciparum malaria is a significant public health problem in Comoros, and artemisinin combination therapy (ACT) remains the first choice for treating acute uncomplicated P. falciparum. The emergence and spread of artemisinin-resistant P. falciparum in Southeast Asia, associated with mutations in K13-propeller gene, poses a potential threat to ACT efficacy. Detection of mutations in the P. falciparum K13-propeller gene may provide the first-hand information on changes in parasite susceptibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 39 publications
3
26
0
Order By: Relevance
“…Additional studies comparing the genetic diversity in K13PD before and after the introduction of ACTs in Africa have generally been consistent with our findings from Uganda, with no significant difference in the proportion of parasites with a NS-SNP before and after the introduction of ACTs (35)(36)(37)(38). However, a report from Kenya described a significant decrease, and one from Comoros described an increase in K13PD polymorphisms following the introduction ACTs (39,40). The nucleotide diversity we report for the K13PD is in scale with that reported from other regions of Africa, as is the presence of an excess of rare alleles (41).…”
Section: Discussionsupporting
confidence: 89%
“…Additional studies comparing the genetic diversity in K13PD before and after the introduction of ACTs in Africa have generally been consistent with our findings from Uganda, with no significant difference in the proportion of parasites with a NS-SNP before and after the introduction of ACTs (35)(36)(37)(38). However, a report from Kenya described a significant decrease, and one from Comoros described an increase in K13PD polymorphisms following the introduction ACTs (39,40). The nucleotide diversity we report for the K13PD is in scale with that reported from other regions of Africa, as is the presence of an excess of rare alleles (41).…”
Section: Discussionsupporting
confidence: 89%
“…Seven mutations were previously detected in isolates from African countries, i.e. D464E (Huang et al 2015a, Madamet et al 2017 (Cooper et al 2015). Three mutations which were previously detected in both Asian and African countries were also detected in this study, i.e.…”
Section: Discussionsupporting
confidence: 80%
“…The identified K13 mutations C580Y, Y493H and R539T were shown to be associated with the delay in parasite clearance both in vitro and in vivo (Ariey et al 2014). However, these mutations were not detected in P. falciparum isolates in African countries (Conrad et al 2014, Cooper et al 2015, Huang et al 2015a, Menard et al 2016b.…”
mentioning
confidence: 91%
“…Several studies have confirmed that some K13-propeller mutations are also markers of slow parasite clearance outside Cambodia, in Thailand, Vietnam, Myanmar, and China (10,26,40,41 Togo, Uganda, and Zambia (55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66). The most frequent mutation in SSA is A578S; however, haplotype analysis does not show evidence of selection of this mutation in the African P. falciparum population and this mutation is present naturally in P. vivax and P. knowlesi [67].…”
Section: Molecular Epidemiologymentioning
confidence: 99%